2020
DOI: 10.1186/s13256-020-02539-x
|View full text |Cite
|
Sign up to set email alerts
|

Complex cytogenetic abnormalities in chronic myeloid leukemia resulting in early progression to blast crisis: a case report

Abstract: Introduction BCR-ABL1, resulting from t(9;22), is the oncogenic driver of chronic myeloid leukemia and the therapeutic target of the disease. Molecular studies have been the gold standard modality for patient assessment since the advent of tyrosine kinase inhibitor therapy. In spite of that, there are cytogenetic abnormalities that can render the disease unresponsive to conventional therapy, thus making cytogenetics an important component of patient management guidelines. Case presentation We present a case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Karyotyping and cytogenetic studies of hematological diseases have shown the prognostic impact of chromosomal abnormalities on the diagnosis and treatment of patients over the last three decades. (Malakzai et al, 2020;Grimwade et al, 2001). WHO categorized the hematological neoplasms, but clonal abnormality detection provides the detail insights of prognostic and therapeutics in malignant or premalignant disorders (Mitelman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Karyotyping and cytogenetic studies of hematological diseases have shown the prognostic impact of chromosomal abnormalities on the diagnosis and treatment of patients over the last three decades. (Malakzai et al, 2020;Grimwade et al, 2001). WHO categorized the hematological neoplasms, but clonal abnormality detection provides the detail insights of prognostic and therapeutics in malignant or premalignant disorders (Mitelman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…New clone of cells can arise from the existing clone of leukemic cells, either spontaneously or during the institution of chemotherapy [ 8 ]. Evolved clone(s) of cells contain new genetic abnormalities either in the form of chromosomal aberrations in the form of abnormalities in chromosome number, chromosomal consistency, loss or gain of chromosomal regions, loss of whole chromosome or genetic mutations [ 6 , 8 ]. Such genetic abnormalities in the new clone of neoplastic cells can transform an initially chemotherapy‐responsive acute leukemia to become chemotherapy‐resistant [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of all the current modalities that are utilized for both diagnostic and prognostic purposes, a significant number of patients do not achieve the therapeutic targets [ 5 ]. Spontaneous clonal evolution results in emergence of clones of neoplastic cells that transforms a previously well‐controlled disease to one that is unresponsive to available therapeutic modalities [ 6 ]. It is very obvious that at cellular and molecular levels, there are many factors, sill unexplored, that take part in intercellular signaling and thus lead to clonal evolution [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, still banding cytogenetic analysis plays an important role in first diagnostics and management of CML [ 22 ]. Besides detection of Ph chromosome, complex chromosomal abnormalities can be identified, which may determine the patient as candidate for alternative and more aggressive therapeutic options, sometimes even leading to allogeneic stem cell transplantation [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%